2012
DOI: 10.4314/thrb.v14i1.10
|View full text |Cite
|
Sign up to set email alerts
|

Key considerations in scaling up male circumcision in Tanzania: views of the urban residents in Tanzania

Abstract: Male circumcision (MC) reduces the risk of sexually transmitted infections (STI) including HIV. The WHO and UNAIDS recommend male circumcision as an additional intervention to prevent HIV infection. Tanzania is embarking on activities to scale up safe male circumcision for HIV prevention and other related health benefits. In line with this, it is crucial to assess views of the population using specific groups. This paper describes perceptions on male circumcision and strategies of enhancing uptake of male circ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2012
2012
2013
2013

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 13 publications
1
4
0
Order By: Relevance
“…The hygiene aspect of medical circumcision appears to be a widespread perceived benefit of the procedure that has been observed in other settings in Africa (Tarimo et al, 2012). Similar findings have emerged in other African countries as well amongst rural and urban populations (Francis, et al, 2012). Older men also mentioned their desire to give their female partners sexual pleasure.…”
Section: Introductionsupporting
confidence: 88%
“…The hygiene aspect of medical circumcision appears to be a widespread perceived benefit of the procedure that has been observed in other settings in Africa (Tarimo et al, 2012). Similar findings have emerged in other African countries as well amongst rural and urban populations (Francis, et al, 2012). Older men also mentioned their desire to give their female partners sexual pleasure.…”
Section: Introductionsupporting
confidence: 88%
“…In addition, the existing norm about male circumcision and the interaction of peers in this community may automatically convince men from the tribes that do not circumcise to perform circumcision. This may be reflected in the diversity of ethnic groups among informants in this study and in the results of a previous study from this population, which showed that 96% of the participants were circumcised [32]. In Ghana, the majority of boys are circumcised because of the desire to conform, which is an important motivation for performing circumcision among them [5].…”
Section: Discussionmentioning
confidence: 78%
“…The findings are drawn from a small number of participants and from a limited geographical area. Also, according to a previous study [ 32 ], male circumcision is a strong norm in this population, which might have influenced the stated perceptions. Therefore, the study informants may not represent the general population.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…This has lead to various stakeholders to recommend male circumcision as a complementary but not a substitute method in HIV prevention. The efforts to upscale male circumcision should be upheld countries where there is an ongoing campaign on male circumcision (Francis et al, 2012).…”
Section: Medical Aspects Of Circumcisionmentioning
confidence: 99%